Uji Mutu Fisik Sediaan Sabun Padat Ekstrak Daun Tin (Ficus carica L.) - Andri Priyoherianto; Elly Purwati; Erna Fitriany (Unversitas Muhammadiyah Mataram, 2023)
The content of flavonoid compounds in tin leaves has the potential to be an alternative source of natural antioxidants. The purpose of this study was to determine the formulation and physical quality test of tin leaf extract solid soap preparations. This research method is an experimental research and method of making soap using the cold process method. Making tin leaf extract solid soap by collecting the ingredients to be extracted using the maceration method with 70% ethanol solvent, carrying out formulations with extract concentrations of 0% 1% and 3% and evaluating the physical quality of solid soap preparations which include organoleptic tests, pH tests, homogeneity test and foam height test on tin leaf extract solid soap. Organoleptic test of solid soap F0 produces a light green color with black mystique perfume, F1 produces a dark green color with black mystique perfume, F2 produces a brownish green color with strawberry perfume. The pH value obtained, which is 9, meets the requirements, the pH range for solid soap for the skin is 9-11. The homogeneity test showed that the fig leaf extract herbal soap with a concentration of 1% and 3% showed no spots, therefore the fig leaf solid soap fulfilled the homogeneity requirements. The soap foam height test showed that soap produced foam (F0= 9.16Ccm, F1= 8cm, F2= 8.16cm).